Implementation Of Multiple Intelligence-Based Character Education To Madrasah Ibtidaiyah Teachers In Gorontalo City - Marhawati, Besse; Masaong, Abd Kadim; Karim, Herlis Setiawan (Faculty of Education Universitas Negeri Malang, 2023)
This article aims to describe: (1) the application of intellectual intelligence-based character education to MI teachers in Gorontalo City, (2) the application of emotional intelligence-based character education to MI teachers in Gorontalo City, and (3) the application of spiritual intelligence-based character education to teachers MI in Gorontalo City. The research method uses a quantitative approach to the type of percentage. The subjects of this study were 30 madrasah ibtidaiyah teachers in the city of Gorontalo. Data collection techniques using questionnaires, observation, and documentation. Data analysis techniques using percentage techniques. The results showed: (1) the application of intellectual intelligence-based character education to MI teachers in Gorontalo City was in good enough criteria, (2) the application of emotional intelligence-based character education to MI teachers in Gorontalo City was in good criteria and (3) application of spiritual intelligence-based character education to MI teachers in Gorontalo City with very good criteria. This shows that the application of multiple intelligence-based character education to primary school teachers in the city of Gorontalo is in good criteria.